The Value Chain Analysis of Tri-Star Toothbrush and Co. - Ahmed, Arif (BRAC Business School, BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.